Corporate social responsibility : perspectives for sustainable corporate governance - Malecki, Catherine (Edward Elgar Publishing, 2018)
Corporate social responsibility (CSR) is setting new missions for companies and shining a welcome light on issues such as the behaviour of board members, shared value, the well-being of stakeholders, the protection of vulnerable individuals and the roles played by public opinion and shareholders. This timely book seeks to lay the foundations for a sustainable corporate governance based on the European Commission definition of CSR as 'the responsibility of enterprises for their impacts on society'. More generally, this sustainable corporate governance responds to some of the pressing challenges of the 21st century, from sustainable finance and climate change to carbon reduction and population growth. The book offers a comprehensive theoretical and educational approach to CSR, with references to key international, European and national texts on this subject. It is written largely from a European and French perspective, but draws comparisons with the United Kingdom and United States. The close relationship between the demands of energy transition and corporate governance and the role of Social Responsibility Investment (SRI) and its relationship with CSR are covered in depth. In addition, the notion of a 'stakeholder', as well as changes in our understanding of this term and its impact on corporate governance, is explored in detail. This significant book offers a theoretical and dynamic approach to CSR, adopting a holistic vision that is both practical and forward-looking. Providing a wealth of reference material and highlighting areas for future research, it is an ideal tool for both students and academics studying CSR.